A combined electrochemical and theoretical study into the effect of 2-((thiazole-2-ylimino)methyl)phenol as a corrosion inhibitor for mild steel in a highly acidic environment - Yilmaz, Nurdane; Fitoz, Alper; Ergun, ÿmit; Emregül, Kaan C. (Elsevier BV, 2016)
Abstract 2-((Thiazole-2-ylimino)methyl)phenol (THYMP) was studied as a corrosion inhibitor for the protection of mild steel in 2 M HCl solution by means of weight loss, polarization, electrochemical impedance spectroscopy and scanning electron microscopy. The potential of zero charge (E pzc ), was also determined for evaluation of the adsorption mechanism. Quantum chemical parameters such as highest occupied molecular orbital energy (E HOMO ), lowest unoccupied molecular orbital energy (E LUMO ), energy gap (οE), dipole moment (μ) etc. were calculated using density functional theory (DFT) at B3LYP/6-31G(d,p) level. Theoretical and experimental results were in fairly good agreement.
Keywords: Mild steel; EIS; Corrosion inhibitor; Polarization; SEM; DFT